Tetrahedral charge and Fe content in dioctahedral smectites. (1st March 2017) - Kaufhold, S.; Stucki, J.W.; Finck, N.; Steininger, R.; Zimina, A.; Dohrmann, R.; Ufer, K.; Pentrák, M.; Pentráková, L.
Natural aluminosilicates can contain Fe in tetrahedral or octahedral coordination. Amongst smectites, tetrahedral iron is known to occur in Fe-rich nontronites but few indications exist for the presence of tetrahedral Fe in smectites of the montmorillonite–beidellite series. A set of 38 different bentonites showed a correlation of tetrahedral charge and Fe content in their smectites. All materials with large tetrahedral charge were rich in Fe. This could be explained by a general tendency of Fe to enter the tetrahedral sheet. To investigate this correlation, nine materials were selected and investigated by Mössbauer, UV-Vis, Fe K pre-edge and EXAFS spectroscopy with respect to tetrahedral Fe (Fe[IV]). The latter two methods were at the detection limit but Mössbauer and UV-Vis spectroscopy provided consistent results indicating the significance of both methods in spite of some scatter caused by the overall small amount of tetrahedral Fe. The results indicate the absence of any relation between Fe content and tetrahedral Fe. Tetrahedral Fe can be present in Fe-poor smectites and absent in the case of Fe-rich materials. This means that Fe-rich montmorillonites have a larger tetrahedral charge which is not caused by Fe[IV] but by Al[IV]. A possible explanation for this indirect relation is based on: the coordination of Al3+ in the weathering/smectite-forming solutions determines the coordination in the precipitates; and the Al[IV/VI] ratio increases with increasing pH. The correlation could thus be explained if the pH of weathering solutions generally was higher in Fe-rich parent smectite rocks than in more acidic smectite parent rocks. The relation between tetrahedral charge and Fe content can probably be explained by different geochemical contexts throughout the formation of smectites which affect the coordination of dissolved Al.